THE RISK MANAGEMENT OF SUSTAINABILITY OF INDUSTRIAL ORGANIZATIONS - M. Kuznetsova (Вестник университета)
The features of risk management of stability of the industrial organizations have been considered. The trends of loss of sustainability have been revealed by the industrial organizations of Russia. Stages of risk management of stability of the organizations have been substantiated. Homogeneous groups of industrial organizations with similar characteristics state have been identified, which increases the efficiency of the risk analysis. The qualitative analysis of risk factors on the basis of the Internet sources and assessment of financial and economic indicators of industrial organizations has been carried out; an array of external and internal factors of risk, affecting sustainability of the industrial organizations, has been created.